2013
DOI: 10.1371/journal.pgen.1003565
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale Analysis of Escherichia coli FNR Reveals Complex Features of Transcription Factor Binding

Abstract: FNR is a well-studied global regulator of anaerobiosis, which is widely conserved across bacteria. Despite the importance of FNR and anaerobiosis in microbial lifestyles, the factors that influence its function on a genome-wide scale are poorly understood. Here, we report a functional genomic analysis of FNR action. We find that FNR occupancy at many target sites is strongly influenced by nucleoid-associated proteins (NAPs) that restrict access to many FNR binding sites. At a genome-wide level, only a subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
243
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(266 citation statements)
references
References 156 publications
(197 reference statements)
21
243
1
1
Order By: Relevance
“…Our evidence also showed that FNR directly regulates the expression of the two-component signal transduction system KguS/KguR, thus likely indirectly regulating other pathogenicity island genes, such as c5038, through KguS/ KguR. It has been well-known that the global regulator FNR in E. coli K-12 controls 122 operons, which are organized into seven regulatory categories (41). To the best of our knowledge, this is the first report showing that FNR controls the expression of a metabolism island in pathogenic E. coli and contributes to bacterial fitness in vivo.…”
Section: Discussionsupporting
confidence: 60%
“…Our evidence also showed that FNR directly regulates the expression of the two-component signal transduction system KguS/KguR, thus likely indirectly regulating other pathogenicity island genes, such as c5038, through KguS/ KguR. It has been well-known that the global regulator FNR in E. coli K-12 controls 122 operons, which are organized into seven regulatory categories (41). To the best of our knowledge, this is the first report showing that FNR controls the expression of a metabolism island in pathogenic E. coli and contributes to bacterial fitness in vivo.…”
Section: Discussionsupporting
confidence: 60%
“…(Table S1). The most prominent anaerobic regulator of E. coli, Fnr normally activates genes under low-oxygen conditions (25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA was coupled to 4.5 l of Cy3 mono-reactive dye (GE Healthcare) according to the manufacturer's protocol and purified with a MERmaid kit. The cDNA was hybridized to a custom E. coli K12 MG1655 tiled genome microarray (Roche NimbleGen) and scanned as described previously (23).…”
Section: Complex Name Left Rightmentioning
confidence: 99%
“…To determine the sequence of these small RNAs, we used them as template for synthesis of firststrand Cy3-labeled cDNA and hybridized the cDNA to a tiled microarray of the E. coli genome (23). After manual filtering of spurious signals, we used MEME to search for common sequence patterns (31).…”
Section: Expression Of Recombinant Sen1-hd In E Coli-previous Inmentioning
confidence: 99%